X-ray micro-computed tomography and ultrasonic velocity analysis of fractured shale as a function of effective stress - Yu, H.; Zhang, Y.; Lebedev, Maxim; Wang, Z.; Li, X.; Squelch, Andrew; Verrall, M.; Iglauer, Stefan (ELSEVIER SCI LTD, 2019)
© 2019 Elsevier Ltd